Effect of passing training variations on the overhand pass on volleyball games - Gunawan, Sani; Muharam, Agum Amung (Jurnal Maenpo : Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi, 2022)
The purpose of this study was to determine the Effect of Variations on Upper Passing Exercises on Volleyball Passing Skills in Volleyball Extracurricular Students at SMP Negeri 3 Manonjaya Kab. Tasikmalaya. The method that the author uses is the experimental method. The population used in this study were extracurricular volleyball students at SMP Negeri 3 Manonjaya Kab. Tasikmalaya. The total population is 35 people. The sample was done randomly by lottery with a total of 20 people. Based on the results of hypothesis testingÂ Â using a statistical approach, the research hypothesis that the author proposes is: "The variation of upper passing practice significantly affects the upper passing skills of volleyball extracurricular students at SMP Negeri 3 Manonjaya Kab. Tasikmalayaâ€ turns out to be accepted or proven. The truth of the results of hypothesis testing is also supported by research data using the t` test which shows the t`count value of 3.4 which is outside the area of acceptance of the hypothesis (t` of 1.73). The acceptance of the hypothesis is suspected because to produce good skill results, it can be done using various forms of exercise or variations of exercise Based on these results, it can be said that training using a variety of exercises is effectively used to improve overhead passing skills, especially for extracurricular students at SMP Negeri 3 Manonjaya Kab. TasikmalayaKeywords: Exercise Variations, Top Passing